High-Frequency Monitoring Reveals Multiple Frequencies of Nitrogen and Carbon Mass Balance Dynamics in a Headwater Stream - Khamis, Kieran; Blaen, Phillip J.; Comer-Warner, Sophie; Hannah, David M.; MacKenzie, A. Rob; Krause, Stefan (Frontiers in Water, 2021)
The uptake of aquatic nutrients can represent a major pathway for their removal from river ecosystems and is a key control on nitrogen and carbon export from watersheds. Our understanding of temporal variability in nutrient mass balance is incomplete as conventional methods for estimating uptake rates are suited to low-frequency analysis. Here, we utilise hourly streamflow, nitrate (NO3--N) and dissolved organic carbon (DOC) to generate near-continuous estimates of nutrient uptake along a 1 km reach in a headwater catchment with a history of agricultural activity. We identify variability in nutrient mass balance at multiple frequencies. Over seasonal timescales, a shift from nitrate release during spring to uptake during autumn was apparent. In contrast, consistent uptake of DOC was observed across the whole monitoring period (i.e. spring – autumn). Both DOC and nitrate uptake were related significantly to environmental variables (river discharge) and antecedent discharge conditions. DOC:nitrate stoichiometry appeared to be a key control on nitrate uptake rates, yet this coupling weakened from summer to autumn as DOC became more abundant and physical controls become more important. Daily cycles in nutrient uptake were evident and at times the investigated reach acted as a net sink of DOC during the day and a source at night. Short-term impacts of storm events on uptake rates varied seasonally but no consistent changes were observed between pre- and post-event conditions, suggesting aquatic communities were resilient to short-term flow disturbances. For the duration of our study, the reach acted as net sink from the water for DOC (-1.7 % of upstream flux) and a net source for nitrate (+ 2.6 %). Even during autumn, when uptake was greatest, mass removal represented <3% of nitrate exported downstream. Our results facilitate new insights into multi-timescale patterns and drivers of stream ecosystem processes, which are essential for developing effective catchment-scale management strategies.